2009
DOI: 10.1016/j.neuroscience.2009.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 2 receptors have a major somatodendritic distribution in vasopressin-containing neurons in the mouse hypothalamic paraventricular nucleus

Abstract: The hypothalamic paraventricular nucleus (PVN) and angiotensin II (AngII) play critical roles in cardiovascular and neurohumoral regulation ascribed in part to vasopressin (VP) release. The AngII actions in the PVN are mediated largely through AngII type 1 (AT1) receptors. However, there is indirect evidence that the functionally elusive central AngII type 2 (AT2) receptors are also mediators of AngII signaling in the PVN. We used electron microscopic dual immunolabeling of antisera recognizing the AT2 recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 107 publications
4
28
0
Order By: Relevance
“…Further work is required to causally link specific RAS receptor subtypes to the AVP elevation, as morphological and functional evidence support roles for both AT 1 and AT 2 receptors in AVP release (reviewed in Ref. 10).…”
Section: R824mentioning
confidence: 99%
See 2 more Smart Citations
“…Further work is required to causally link specific RAS receptor subtypes to the AVP elevation, as morphological and functional evidence support roles for both AT 1 and AT 2 receptors in AVP release (reviewed in Ref. 10).…”
Section: R824mentioning
confidence: 99%
“…Two major mechanisms have been documented that account for the blood pressure effects of brain angiotensin. First, actions of the RAS within the supraoptic (SON) and paraventricular hypothalamic nuclei (PVN) stimulate the production and release of arginine vasopressin (AVP, also known as antidiuretic hormone, ADH, or argipressin) (4,10,17,31,51,53,62). Second, hindbrain and brain stem actions of the RAS alter baroreflex function and sympathetic output (22,26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 10 years ago, co-localization studies using electron microscopic dual immunolabeling of the AT2R and AVP indicated for the first time that there is a co-localization of AT2R and AVP containing neurons in the PVN [44]. Since the PVN is the main area of AVP synthesis, this observation pointed to a role of the AT2R in the control of AVP generation.…”
Section: At2r and Regulation Of Vasopressin Releasementioning
confidence: 99%
“…Since the PVN is the main area of AVP synthesis, this observation pointed to a role of the AT2R in the control of AVP generation. Interestingly, the authors of this initial study reported localization of AT2R mainly on neuronal processes in the PVN, but not or only very rarely on soma [44]. The same pattern was found by our group using the AT2R-eGFP-BAC-transgenic reporter-mouse: AT2R-positive, fluorescent green staining was not detectable on the soma of AVP neurons within the PVN, but on processes and nerve terminals arising from AT2R-positive cell bodies in the peri-PVN area, which extended into the PVN and synapsed onto AVP neurons [17,19].…”
Section: At2r and Regulation Of Vasopressin Releasementioning
confidence: 99%